A new theoretical analysis of the debt financing decision: European evidence from industry data - Bego\~na Álvarez García; Lucía Boedo Vilabella; Dolores Lagoa Varela (Atlantic Review of Economics, 2012)
The objective of this paper is to investigate the process of company's debt accumulation in different European countries throughout the last decade. As a preliminary step to the empirical study, a new theoretical framework is proposed relative to capital structure, where the decision of going to debt does not only depend on the firm's characteristics, but also on cultural, institutional and psychological factors. In the analysis of the debt evolution over time, we take special notice of the difference between rich and poor countries and, among the latter, we focussed our attention on the behaviour of Spain in contrast to the rest. Given that the period analysed includes the eruption of the crisis, the paper permits the observation of each country's reaction. Some interesting conclusions have been obtained, such as the most significant increase in debt in poor countries has occurred in the second half of the decade, and that Spain and Portugal show a different performance from many others in terms of the variables analysed. Altogether, the results indicate, in our opinion, the importance of institutional and cultural characteristics as factors which explain company behaviour relative to debt.
Keywords: G32; 330; enterprise debt finance; capital structure determinants; financial crisis; European indebtedness